STUDI PERBANDINGAN KARAKTER TANGGUNG JAWAB DALAM PEMBELAJARAN ONLINE MATA PELAJARAN PKN ANTARA SISWA LAKI-LAKI DAN PEREMPUAN DI SMA AL HUDA PEKANBARU - Indriani, Rani; Hambali, Hambali; Separen, Separen (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by the spread of covid-19 which has an impact on various aspects of life including the field of education. Online learning has both positive and negative impacts in the learning process. Ineffective online learning will cause students to tend to be lazy and forget about their learning responsibilities. In the context of education, learning responsibilities have a very important role in efforts to improve the effectiveness of online learning. In this study researchers examined the comparison of the character of student responsibility in online learning of PKn subjects between male and female students at Al Huda Pekanbaru High School. The method used in this study was a comparative and quantitative method. The population in this study was all students of class XII majoring in IPA and IPS at Al Huda Pekanbaru High School as many as 81 students, consisting of 29 male students and 52 female students. Sampling methods use sampling quota techniques. The sample taken in this study was 58 students. It consists of 29 men students and 29 female students. The data collection technique used in this study is to use observations and questionnaires. The data analysis technique used in this study is to use statistical tests. The statistical test result was to compare two data groups namely male and female students with a result of 0.017 and a score of 0.017 < 0.05 (2-tailed < 0.05), then Ha was accepted and Ho was rejected. It can be concluded that there is a difference in the character of responsibility in online learning of PKn subjects between male and female students at Al Huda Pekanbaru High School.Key Words: Comparison, Responsibility Character, Online Learning, Students.